Dramatic evolution of body length due to postembryonic changes in cell size in a newly discovered close relative of Caenorhabditis elegans. Issue 4 (16th July 2018) - Woodruff, Gavin C.; Willis, John H.; Phillips, Patrick C.
Abstract: Understanding morphological diversity—and morphological constraint—has been a central question in evolutionary biology since its inception. Nematodes of the genus Caenorhabditis, which contains the well‐studied model organism C. elegans, display remarkable morphological consistency in the face of extensive genetic divergence. Here, we provide a description of the broad developmental patterns of a newly discovered species, C . sp. 34, which was isolated from fresh figs in Okinawa and which is among the closest known relatives of C. elegans . C . sp. 34 displays an extremely large body size; it can grow to be nearly twice as long as C. elegans and all other known members of the genus. Observations of the timing of developmental milestones reveal that C . sp. 34 develops about twice as slowly as C. elegans . Measurements of embryonic and larval size show that the size difference between C . sp. 34 and C. elegans is largely due to postembryonic events, particularly during the transition from larval to adult stages. This difference in size is not attributable to differences in germ line chromosome number or the number of somatic cells. The overall difference in body size is therefore largely attributable to changes in cell size via increased cytoplasmic volume. Because of its close relationship to C. elegans, the distinctness of C . sp. 34 provides an ideal system for the detailed analysis of evolutionary diversification. The context of over 40 years of C. elegans developmental genetics also reveals clues into how natural selection and developmental constraint act jointly to promote patterns of morphological stasis and divergence in this group.